Factor analysis of perceived omnichannel customer experience dimensions on satisfaction and loyalty Among Citilink Airline users - Evita Frisdiana Jaya Wardani; Ronald, Ronald; Amelia, Amelia (Jurnal Ekonomi, 2024)
In the midst of increasingly tight competition between airlines, there are many efforts being made by airlines, including Citilink. As one of the airline companies in Indonesia, Citilink remains stable in competing with other airlines. Namely in finding, attracting and retaining customers to satisfy service users, especially through service. Companies must place an orientation on customer satisfaction as the main goal where the service performance must be in accordance with the level of consumer expectations. The main key to winning the competition is providing value and satisfaction to customers through delivering quality products and services. Data from this research was collected using a questionnaireelectronicGoogle form from 240 respondents who have used Citilink airline in Surabaya. This research uses SPSS to assess the relationship between variables. This research shows that the Perceived Dimension FactorOmni ChannelCustomersExperiencehas a significant effect on Satisfaction and Loyalty.